2004
DOI: 10.1081/ese-200034763
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Recovery of Copper from Printed Circuit Boards of Waste Computer by Acidithiobacillus ferrooxidans

Abstract: The bioleaching of copper contained in the printed circuit boards (PCB) of waste computers by A. ferrooxidans was studied. The Fe oxidation rates by A. ferrooxidans in the 9K medium supplemented with the leachate of PCB (0.15-0.13 g L(-1) d(-1)) were similar to that in the 9K medium without the leachate (0.15 g L(-1) d(-1)). This finding suggests that the leachate of PCB did not seriously affect the bioleaching process by this bacterium. The amount of copper leached from PCB shreds increased with the addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 9 publications
3
22
0
2
Order By: Relevance
“…Recent research has shown that the action of acids in the bioleaching process is of influence on the solubilization rate of the metal [75,87]. According to Saidan et al [75], in a pH of 2, bio-metabolized organic acids lead to a better dissolution of the copper coming from printed circuit boards than sulfuric acid, which is the result of bacterial action.…”
Section: Department Of Chemical Engineering Polytechnic School Univmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent research has shown that the action of acids in the bioleaching process is of influence on the solubilization rate of the metal [75,87]. According to Saidan et al [75], in a pH of 2, bio-metabolized organic acids lead to a better dissolution of the copper coming from printed circuit boards than sulfuric acid, which is the result of bacterial action.…”
Section: Department Of Chemical Engineering Polytechnic School Univmentioning
confidence: 98%
“…Agitated flasks [62] Sulfobacilllus thermosulfidooxidan, Thermoplasma acidophilum, and Sulfobacilllus acidophilus [63] Sulfobacilllus thermosulfidooxidans and Thermoplasma acidophilum Columns [65] Acidophilus bacteria Agitated flasks [59] Acidithiobacillus ferrooxidans [89] Acidithiobacillus ferrooxidans [87] Sulfobacillus thermosulfidooxidans and unidentified acidophilus bacteria (code A1TSB) […”
Section: Acidithiobacillus Thiooxidans and Acidithiobacillus Ferrooximentioning
confidence: 99%
“…Yapılan araştırmalar incelendiğinde, eatıkların hidrometalurjik yöntemle geri kazanımı 1960'lara kadar dayanmaktadır ve bu proseslerde metal içeriği kuvvetli sülfürik asit, hidroklorik asit, nitrik asit, aqua regia ve alkalileri içeren liç çözeltilerinde çözülebilmektedir [33]. Son 20 yılda ise yapılan araştırmalar da bioliç yöntemlerinin e-atıklardan metallerin kazanımında etkili rol oynadığı da ortaya konmuştur [33][34][35][36].…”
Section: Kimyasal Yöntemlerunclassified
“…Estudos de lixiviação bacteriana (18)(19)(20)(21)27) reportam taxas de extração acima de 70% com condições de agitação variando entre 150 rpm a 250 rpm; porém, utilizando velocidades de rotação de 150 rpm e 160 rpm, a extração do cobre diminu para menos de 60%. Lixiviação bacteriana de sucata eletrônica: influência dos parâmetros de processo A Figura 4 mostra que o aumento na concentração inicial de íon ferroso não aumenta a extração de cobre, como seria esperado, já que atividade biológica está estritamente ligada à oxidação do íon ferroso.…”
Section: +3unclassified